Using conceptual blending to describe how students use mathematical integrals in physics - Hu, Dehui; Rebello, N. Sanjay (My University, 2013)
Calculus is used across many physics topics from introductory to upper-division courses. The fundamental concepts of differentiation and integration are important tools for solving real-world problems involving nonuniformly distributed quantities. Research in physics education has reported students’ lack of ability to transfer their calculus knowledge to physics. In order to better understand students’ deficiencies, we collected data from group teaching or learning interviews as students solved physics problems requiring setting up integrals. We adapted the conceptual blending framework from cognitive science to make sense of the ways in which students combined their knowledge from calculus and physics to set up integrals. We found that many students were not able to blend their mathematics and physics knowledge in a productive way though they have the required mathematics knowledge. We discussed the productive and unproductive blends that students created when setting up integrals. The results of the study also suggested possible strategies to shifting students’ constructing of blends to more powerful ones.
Keywords: Calculus; Physics education; Integrals; Conceptual blending